2-NBDG Uptake in Gossypium hirsutum in vitro ovules: exploring tissue-specific accumulation and its impact on hexokinase-mediated glycolysis regulation - Shamshoum, Melina; Kuperman, Ofir Aharon; Shadmi, Sapir Korman; Itkin, Maxim; Malitsky, Sergey; Natalio, Filipe (Frontiers in Plant Science, 2023)
Fluorescent glucose derivatives are valuable tools as glucose analogs in plant research to explore metabolic pathways, study enzyme activity, and investigate cellular processes related to glucose metabolism and sugar transport. They allow visualization and tracking of glucose uptake, its utilization, and distribution within plant cells and tissues.This study investigates the phenotypic and metabolic impact of the exogenously fed glucose derivative, 2-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)-2-deoxyglucose) (2-NBDG) on the fibers of Gossypium hirsutum (Upland cotton) ovule in vitro cultures. The presence of 2-NBDG in the culture medium did not lead to macroscopic morphological alterations in ovule and fiber development or to the acquisition of fluorescence or yellow coloration. Confocal laser scanning microscope imaging and chromatographic analysis of cotton ovules' outer rim cross-sections showed that the 2-NBDG is transported from the extracellular space and accumulated inside some outer integument cells, epidermal cells, and fertilized epidermal cells (fibers), but is not incorporated into the cell walls. Untargeted metabolic profiling of the fibers revealed significant changes in the relative levels of metabolites involved in glycolysis and upregulation of alternative energy-related pathways.To provide biochemical and structural evidence for the observed downregulation of glycolysis pathways in the fibers containing 2-NBDG, kinetics analysis and docking simulations were performed on hexokinase from G. hirsutum (GhHxk). Notably, the catalytic activity of heterologously expressed recombinant active GhHxk exhibited a fivefold decrease in reaction rates compared to D-glucose. Furthermore, GhHxk exhibited a linear kinetic behavior in the presence of 2-NBDG instead of the Michaelis-Menten kinetics found for D-glucose. Docking simulations suggested that 2-NBDG interacts with a distinct binding site of GhHxk9, possibly inducing a conformational change.These results highlight the importance of considering fluorescent glucose derivatives as ready-to-use analogs for tracking glucose-related biological processes. However, a direct comparison between their mode of action and its extrapolation into biochemical considerations should go beyond microscopic inspection and include complementary analytical techniques.